CONCEPTUALIZATION OF SUSTAINABLE DEVELOPMENT OF LOCAL COMMUNITIES - Сарић, Радојица; Рољевић, Светлана; Грујић, Биљана (Economics of Agriculture, 2011)
At the beginning of XXI century, creators and advocates of socio-economic development on local level are striving to, on one hand, revitalize the values of local communities and the path of their identity development in the context of the process of globalization, and on the other, they are pointing to the potentials of local communities in creating and carrying out integral sustainable development. Conceptualization of sustainable development of local communities requires that the factors of socio-economic development and protection of environment, in the framework of the community on local level, be regarded in systematic and interactive way through the holistic approach, harmoniously. Accordingly, local community contributes and facilitates the realization of integral sustainable development of the country and acquires a signifcant role in the process of the improvement of the quality of life of its inhabitants.